Influence of A-site deficiency on electrical characteristics of barium strontium titanate perovskite dielectrics - Natthaphon Raengthon (2018)
© 2018 Author(s). Improvement of dielectric properties and insulation resistance are important for the development of high-performance dielectric materials. Various techniques can be used in order to improve the performance of such materials. The effect of A-cation deficiency on the electrical properties of barium strontium titanate ceramics is an interesting topic of investigation. Thus, this study examined the stoichiometric, 0.01 mol Ba-deficient, and 0.01 mol Sr-deficient compositions of (Ba0.8Sr0.2)TiO3 ceramics. Changes in the dielectric characteristics were observed in the 0.01 mol Ba-deficient and 0.01 mol Sr-deficient compositions. The characteristics of electrical conduction revealed by impedance analysis are different at high temperatures when Ba-deficiency and Sr-deficiency are introduced to the dielectrics. The Ti4+ state for the Ba-deficient composition is maintained. However, the Ti4+ state partially changes to the Ti3+ state, giving rise to the polaron hopping conduction process for Sr-deficient composition. Therefore, this study shows that a minor deviation of the A-cation from stoichiometry can induce a different conduction process while maintaining the dielectric permittivity characteristics.